DNA polymerase alpha from the nuclear matrix of cells infected with simian virus 40. - Jones, C (1982)
The nuclear matrix prepared from normal, simian virus 40 (SV40)-infected, and SV40-transformed cells contained DNA polymerase activities. Approximately 12% of the total DNA polymerase activities in isolated nuclei remained with the nuclear matrix. alpha-polymerase was the major matrix DNA polymerase activity as judged by sensitivity to various inhibitors: aphidicolin, dideoxy-TTP, and N-ethylmaleimide. Approximately 2-4 fold higher DNA polymerase activity was detected in matrices obtained from lytically infected and virus-transformed cells than that found in normal cells. In lytically infected cells, 30-50% of the matrix-bound DNA polymerase activity solubilized by sonication co-sedimented with majority of the matrix T-antigen, and was co-precipitated with anti-T sera. The results suggest that alpha-polymerase and viral T-antigen may form a functional complex in the matrix.